COMPETENCY OF ELEMENTARY SCHOOL TEACHERS IN DESIGNING INSTRUCTIONAL DESIGN IN THE AREA OF BRANCH EDUCATION DEPARTMENT IN GEMPOL PASURUAN - FIRDAUSYA, KANIA (Jurnal Mahasiswa Teknologi Pendidikan, 2015)
Competency is an important ability which must be had and mastered by teachers in helping their task and responsible. There are four basic standards which must be mastered by the teachers, one of them is pedagogical competency. Designing learning plan is classified as pedagogical competency. Instructional design is arranged in the form of lesson plan. The success of students’ learning is completely considered by the instructional design made by the teachers. The quality of instructional design reflects the readiness level of the teachers in teaching the students. This research aims to know the elementary school teachers’ competency in designing instructional in the area of education department in Gempol Surabaya. This study is an evaluation research. The subject of this study is the teachers of Elementary school which consist of 35 people. The model of evaluation program which is used in this research is CIPP evaluation model. Data collection method of this research is through questionnaire, instrument of score, interview and documentation. While the technique of data analysis used in this study is descriptive statistic. The evaluation result which got from teaching experience more than 10 years show that the score got was 35,54 ; the teaching experience 5-10 years show that the score got was 37,82, teaching experience less than 5 years show that the score got was 36,50. It is categorized as a good result. The average score got from women teachers was 36,79 with good category. While the average score got from men teachers was 37,57 with good category. The average score got from teachers who have certificated was 37,18 with good category. While the average score got from teachers who have not certificated was 36,62 with good category. It can be concluded that the competency of elementary school teachers in designing learning can be categorized as a good way with differences in teaching experience, sex and sertification status. The recomendation that can be given is the teachers should increase their competency in formulating indicator and the purpose of learning, arrange the steps of learning and scoring. Key words: Competency of Teachers, Instructional Design, CIPP Model